Review of Environmental, Economic And Policy Aspects of Biofuels - Rajagopal, Deepak (The World Bank, 2007)
The world is witnessing a sudden growth in production of biofuels, especially those suited for replacing oil like ethanol and biodiesel. This paper synthesizes what the environmental, economic, and policy literature predicts about the possible effects of these types of biofuels. Another motivation is to identify gaps in understanding and recommend areas for future work. The analysis finds three key conclusions. First, the current generation of biofuels, which is derived from food crops, is intensive in land, water, energy, and chemical inputs. Second, the environmental literature is dominated by a discussion of net carbon offset and net energy gain, while indicators relating to impact on human health, soil quality, biodiversity, water depletion, etc., have received much less attention. Third, there is a fast expanding economic and policy literature that analyzes the various effects of biofuels from both micro and macro perspectives, but there are several gaps. A bewildering array of policies - including energy, transportation, agricultural, trade, and environmental policies - is influencing the evolution of biofuels. But the policies and the level of subsidies do not reflect the marginal impact on welfare or the environment. In summary, all biofuels are not created equal. They exhibit considerable spatial and temporal heterogeneity in production. The impact of biofuels will also be heterogeneous, creating winners and losers. The findings of the paper suggest the importance of the role biomass plays in rural areas of developing countries. Furthermore, the use of biomass for producing fuel for cars can affect access to energy and fodder and not just access to food